Large scale syntheses of colloidal nanomaterials. (February 2017) - Saldanha, Pearl L.; Lesnyak, Vladimir; Manna, Liberato
Graphical abstract: Highlights: Main large-scale colloidal syntheses of various nanomaterials are summarized. Nanomaterials reviewed vary from noble metals to metal oxides and chalcogenides. One-batch syntheses are divided into heat-up and hot-injection methods. Continuous syntheses are represented by tubular and rotating disc (tube) reactors. Examples of each approach are discussed covering simple and more complex materials. Abstract: Nanoscale materials have long promised to revolutionize science and technology, with claims being sustained by both the advances in their fabrication and by the many fundamental studies that have been carried out to date, which have revealed fascinating properties when materials dimensions shrink all the way down to a few hundreds/thousands of atoms. In this ongoing hype, on one side we have the futuristic views and promises of ubiquitous devices in which the operating units will be eventually scaled down to individual atoms or molecules. On the other side, we have the more realistic (and already unfolding) scenario represented by nanoscale materials making their way in a wide variety of applications (not always and not necessarily flagged as "high-tech") where downsizing truly brings about new or improved features that can be immediately exploited for some practical use. These applications have encompassed fields as disparate as medicine, biology, energy conversion and storage, catalysis, sensing, nanocomposite engineering, cosmetics, to cite the most popular ones. For a new technology to be pervasive and disruptive, the costs associated to the fabrication, the characterization and the assemblage of its key components have to drop quickly over time, while at the same time the material quality and the reproducibility of the various processes must keep improving. In the case of nanomaterials, we have not yet witnessed such an ubiquitous revolution, and one of the reasons is probably the lack of straightforward and reproducible synthetic protocols providing large amounts of nanomaterials and thus capable of efficient up-scaling to fulfil industrial needs. Another reason likely resides in the growing concern that nanomaterials will pose new threats to the environment, but this aspect will not be investigated here. In this review, we will touch upon the critical feature of nanomaterials science and engineering dealing with the high throughput synthesis, with a focus on materials prepared in the liquid phase, where the expertise of the authors of this review lays. As a note of caution to the reader, we will not cover in depth all existing approaches to large scale syntheses. Our discussion will be instead a broad summary of the main types of synthetic approaches developed to date, and which we believe will be useful to scientists and engineers who are approaching the fabrication of nanomaterials with an eye on their use in large-scale, industrial applications. The review has been written according to the principle "from the simple to the complex": it begins with the simplest one-batch heat-up synthesis approach, followed by hot-injection methods and ends by discussing the more sophisticated continuous flow syntheses of nanoparticles. Similarly, in each section, wherever possible, the discussion will start from simpler compounds, (for example, one-component noble metal nanocrystals), and will then move on to more complex structures (from binary to ternary and even quaternary compounds, which will be mainly metal oxides and chalcogenides).